430. The First Case Reports of Leptospirosis and Melioidosis in the Aftermath of Hurricanes Irma and Maria—Saint Thomas/Saint John District, US Virgin Islands, September–October 2017. (26th November 2018) - Hunte-Ceasar, Tai; Guendel, Irene; Ekpo, Lisa Laplace; Harrison, Cosme; Ellis, Brett; Davis, Michelle; Ellis, Esther
Abstract: Background: Following Hurricanes Irma and Maria, the first cases of leptospirosis ( n = 1) and melioidosis ( n = 2) were identified in the US Virgin Islands (USVI). Leptospirosis and melioidosis are potentially fatal bacterial diseases caused by Leptospira species and Burkholderia pseudomallei, respectively; both are found in contaminated water/soil and outbreaks have been documented following extreme weather events. Methods: Querying the USVI arbovirus syndromic surveillance system and Emergency Department (ED) records from two hospitals, we identified patients in the 2.5 months post-hurricanes demonstrating symptoms consistent with leptospirosis/melioidosis. Available patient blood samples underwent rapid diagnostic testing (RDT) for anti- Leptospira IgM and were sent to the US Centers for Disease Control and Prevention for confirmatory microscopic agglutination testing (MAT). A subset were tested with a B. pseudomallei antigen RDT, and water collected from sites of potential Leptospira -contamination were tested by PCR. Results: An initial query of the syndromic surveillance database yielded 17 patients warranting testing; 15 available patient samples were tested for leptospirosis and were negative (2 tested for melioidosis—negative). Following efforts to enhance this system to proactively detect leptospirosis/melioidosis, 15 additional patient samples were obtained and tested for leptospirosis; one tested positive. We reviewed 5, 220 ED charts, identifying six patients warranting testing; five available patient samples were tested for leptospirosis; one tested positive (1 tested for melioidosis—negative). Altogether, as of April 2018, there are threeleptospirosis and two melioidosis confirmed cases in USVI. One of threewater samples collected from sites associated with patients with leptospirosis tested PCR-positive for Leptospira species. Conclusion: This investigation documents the first cases of leptospirosis and melioidosis in USVI and demonstrates how USVI's surveillance system was adapted to establish ongoing leptospirosis/melioidosis surveillance. Collectively, although not confirmed by detection of B. pseudomallei in the environment, both leptospirosis and melioidosis may be endemic in the USVI. Disclosures: All authors: No reported disclosures.